Phương pháp xây dựng thuật toán điều khiển robot tọa độ cầu khớp phẳng trên mô hình động học theo ba phương x, y, z - Hùng, Lê Minh; Huy, Phạm Khắc (Journal of Computer Science and Cybernetics, 2016)
Basing on dynamic paprameters as: speeds, translations on three dimensions and morring trajectory of distinetive point have tomade algorithm to control industrial Robot, that is working in zone with plane – spherical coordinate.